Kedudukan Pejabat Kepala Desa dalam Penyelenggaraan Pemerintahan Desa - Arief Sumeru (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2016)
This research was conducted to determine status and legal consequences of village head on the village management in accordance with the provisions of the village legislation. This research approach used normative juridical approach in the sense of examining norms and rules relating to issues to be discussed. Supporting data were secondary data that is obtained from library, legislation in force, and theories that exist in the literature relating to the village. The data collection is obtained by organizing a literature study (Library Research). This research result showed that the presence village head aimed to implement village government in accordance with the provisions of the legislation in force and obtained legal certainty to the community.